Exploring the Role of Artificial Light and Tanning for Skin Cancer - Majid, Muhammad; Abdul Qayoom; Haider, Ali (Indus Journal of Bioscience Research, 2024)
Skin cancer is a complex health condition with a high mortality rate all over the world. The present review article examines the relationship between artificial light exposure, tanning practices, and skin cancer. Artificial light exposure and tanning practices have been linked to various health concerns, particularly skin cancer. Artificial light sources that initiate and progress skin cancers are blue light, laptops, smartphones, and personal computers, leading to significant impacts on the human body. Artificial light exposure and tanning practices have been linked to various health concerns, particularly skin cancer. Both artificial light sources, such as tanning beds) and natural sunlight emit UVA and UVB rays, which can damage DNA in skin cells, leading to mutations that can develop into skin cancer. Tanning beds, in particular, pose a significant risk due to their high levels of UVA radiation. In addition, skin cancer was induced only in the mice exposed to blue light. Long-term blue light irradiation also increased the migration of neutrophils and macrophages involved in carcinogenesis in the skin. The review article also summarized the mechanisms of action of these factors in the progression and development of skin cancer as well.